Review of the aetiologies of central nervous system infections in Vietnam - Brindle, Hannah E.; Choisy, Marc; Christley, Robert; French, Neil; Griffiths, Michael; Thai, Pham Quang; van Doorn, H. Rogier; Nadjm, Behzad (Frontiers in Public Health, 2025)
Central nervous system (CNS) infections are an important cause of morbidity and mortality in Vietnam, with many studies conducted to determine the aetiology. However, the cause remains unknown in a large proportion of cases. Although a systematic review of the aetiologies of CNS infections was conducted in the Mekong region, there are no known published reviews of the studies specifically in Vietnam. Here, we review the cause of CNS infections in Vietnam while also considering the potential aetiologies where a cause was not identified, based on the literature from the region. In particular, we focus on the most common pathogens in adults and children including Streptococcus suis which is associated with the consumption of raw pig products, and Japanese encephalitis virus, a mosquito-borne pathogen. We also discuss pathogens less commonly known to cause CNS infections in Vietnam but have been detected in neighbouring countries such as Orientia tsutsugamushi, Rickettsia typhi and Leptospira species and how these may contribute to the unknown causes in Vietnam. We anticipate that this review may help guide future public health measures to reduce the burden of known pathogens and broaden testing to help identify additional aetiologies.